Application of SemIoTica to the Development of a Prototype of an Intelligent System with IoT in Single-Family Aquaponics at the Tecno Academia Popayán - López Erazo, Oscar Santiago (2024)
The increasing adoption of Internet of Things (IoT) technologies in agriculture has led to improved decision-making processes. However, deploying IoT devices in agricultural systems raises concerns about security vulnerabilities and potential cyber threats. In this context, SemIoTica emerges as a method to systematically identify and mitigate security risks in IoT solutions for agriculture. This paper presents a case study that applies the methodology to identify the security vulnerabilities of a prototype aquaponics system, a tangible example of IoT application in smart agriculture. SemIoTica comprises four steps: (i) scenarios are described for the intended software, (ii) scenarios with incorrect uses of the system are described, (iii) these scenarios are translated into security scenarios using a set of rules, and (iv) the security scenarios are refined. Therefore, based on SemIoTica's four-step approach, correct and incorrect system use scenarios were systematically analyzed, and security scenarios were derived and re-fined to address the identified vulnerabilities. This paper presents an empirical application of the methodology in identifying and mitigating security risks in IoT agriculture, providing valuable information for developers and agriculture practitioners. Future approaches from this research may explore further refinement of security analysis methodologies and the development of robust cybersecurity measures tailored to the unique challenges of IoT applications in agriculture.